2002
DOI: 10.1007/s11661-002-0236-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes in order and texture during annealing of heavily cold-rolled Ni3Al(B,Zr) alloy

Abstract: This article describes the changes in order and texture of a 73 pct cold-rolled Ni 3 Al(B, Zr) alloy after it is subjected to recrystallization annealing. In the initial stages of annealing, the deformed starting material undergoes both recovery and reordering. This is followed by recrystallization with continued annealing. The cold-rolled material, which has a DO 22 structure, undergoes a change in order during the recovery stage, leading to the formation of the earlier L1 2 structure. This is accompanied by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…One such interesting example can be seen in a Ni 3 Al-based duplex alloy. [17,18] In the present case, the order parameter increased again as soon as the material was subjected to heat treatment and remained almost constant thereafter. This observation clearly indicates that the so-called bcc ferrite phase of this steel is basically an ordered DO 3 phase.…”
Section: ½1supporting
confidence: 46%
“…One such interesting example can be seen in a Ni 3 Al-based duplex alloy. [17,18] In the present case, the order parameter increased again as soon as the material was subjected to heat treatment and remained almost constant thereafter. This observation clearly indicates that the so-called bcc ferrite phase of this steel is basically an ordered DO 3 phase.…”
Section: ½1supporting
confidence: 46%
“…X-ray diffraction (XRD) study and textural changes during annealing have been reported elsewhere. [1] The present report deals mainly with the transmission electron microscopic study and recrystallisation kinetics.…”
Section: Methodsmentioning
confidence: 99%
“…This has been reported in an earlier article. [1] The very first grains to recrystallize during annealing were found to be small grains of fcc ␥, preferentially in the shear band regions. This has also been reported in the article.…”
Section: A Microstructural Changesmentioning
confidence: 97%
See 2 more Smart Citations